2023
DOI: 10.1002/aenm.202300719
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Chain‐Guided Ion Transport in Aqueous Electrolytes of Zn‐Ion Batteries

Yan Wu,
Tian Zhang,
Lina Chen
et al.

Abstract: As a promising candidate for next‐generation energy storage devices, Zn metal battery excels with their good safety, high specific capacity, and economic attractiveness. However, it still suffers from a narrow electrochemical window, notorious dendrite formation, and sluggish Zn ion transfer. Aqueous electrolyte engineering has been regarded as an effective way to improve these. It is shown that by adding sodium polystyrene sulfonate (PSS) polymers into a dilute 1 m Zn(OTf)2 aqueous electrolyte, compact water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…This may be due to the occurrence of Al 3+ embedding and ejection. 33,38 Further ex-situ XPS studies were carried out, and the Al 2p peak showed the same results as XRD, becoming less Al during charging and more Al during discharging (Figure 4d). During the discharging process the Al ions start to insert into the cathode again and the peaks start to move in the opposite direction again, and the spacing of the (022) crystal plane is propped up again.…”
Section: ■ Results and Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…This may be due to the occurrence of Al 3+ embedding and ejection. 33,38 Further ex-situ XPS studies were carried out, and the Al 2p peak showed the same results as XRD, becoming less Al during charging and more Al during discharging (Figure 4d). During the discharging process the Al ions start to insert into the cathode again and the peaks start to move in the opposite direction again, and the spacing of the (022) crystal plane is propped up again.…”
Section: ■ Results and Discussionmentioning
confidence: 62%
“…A ex-situ XRD was done on the cathode (Figure b), and the movement of the peak can be seen when magnified (Figure c).There is a regular movement; that is, the peak red-shifts when charging and blue-shifts when discharging. This may be due to the occurrence of Al 3+ embedding and ejection. , Further ex-situ XPS studies were carried out, and the Al 2p peak showed the same results as XRD, becoming less Al during charging and more Al during discharging (Figure d). During the discharging process the Al ions start to insert into the cathode again and the peaks start to move in the opposite direction again, and the spacing of the (022) crystal plane is propped up again .…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations